Estimation levels of prostate-specific antigen, interleukin-8, oxidative stress and some inflammatory markers in sera of benign prostatic hyperplasia patients who have smoking habits as a risk factor - Al-Barzinj, Ruqaya Mohammed Ghareeb Taher (Cellular and Molecular Biology, 2020)
Benign prostatic hyperplasia (BPH) is a common multifactorial inflammatory disease of older men, defined by increased growth of prostate epithelial and stromal cells. Elevation serum levels of Interleukin-8 (IL-8), oxidative stress and inflammatory markers represent predictive surrogate markers of the disease progression in smoker BPH patients. A total of 86 BPH patients and 54 control subjects were admitted to the urology unit, Rizgary Teaching Hospital in Erbil City, Iraq between January and June 2020. Sera levels of prostate-specific antigen(PSA), IL-8, malondialdehyde (MDA), high sensitive C-reactive protein (hs-CRP), testosterone and some biomarkers concentrations were measured in the patients according to instructions of manufacturers. Patients and controls were categorized into groups according to smoking status (smokers and non-smokers). The sera levels of PSA, IL-8 and inflammatory markers like oxidative stress(MDA), hs-CRP and testosterone in every smoker subgroup (BPH patients and control) increased compared to the same non-smoker subgroups and significantly increased compared with non-smoker control (p<0.05). PSA demonstrated a significant positive correlation with the following terms, IL-8, MDA, hs-CRP, testosterone and low-density lipid (LDL)(p<0.05) and, insignificant negative correlation with high-density lipoprotein(HDL), (p>0.05). The current study demonstrated mounting evidence to support the role of smoking in the pathophysiology of BPH through elevation levels of inflammatory and oxidative stress biomarkers in sera of BPH patients.